Asymmetric Organocatalyzed Transfer Hydroxymethylation of Isoindolinones Using Formaldehyde Surrogates - Svestka, David; Bobal, Pavel; Waser, Mario; Otevrel, Jan (Organic letters, 2024)
The piperidine-based Takemoto catalyst has been successfully employed in a novel asymmetric transfer hydroxymethylation of activated isoindolinones, allowing us to prepare the enantioenriched hydroxymethylated adducts in good to excellent yields (48-96%) and enantiopurities (81:19-97:3 e.r.). To increase the reaction rate without compromising the selectivity, carefully optimized formaldehyde surrogates were employed, providing a convenient source of anhydrous formaldehyde with a base-triggered release. The substrate scope, including 34 entries, showed the considerable generality of the asymmetric transformation, and most entries exhibited complete conversions in 24-48 h. A scale-up experiment and multiple enantioselective downstream transformations were also carried out, suggesting the prospective synthetic utility of the products.